Exploring patterns of principal judgments in teacher evaluation related to reported gender and years of experience. (June 2019) - Wind, Stefanie A.; Jones, Eli; Bergin, Christi; Jensen, Kurtis
Highlights: Construct-irrelevant factors often threaten the fairness of classroom observations. We compared ratings over teacher demographics and similarity with principals. Principals' ratings varied by gender, experience, and school level. Principals' demographic similarity to teachers did not affect ratings. Abstract: Meaningful interpretation of teacher evaluation based on classroom observation depends on the degree to which principals' judgments are free from errors and systematic bias. Previous researchers have identified factors that may influence classroom observation ratings, including characteristics of students in the classrooms being observed. In this study, we explored the influence of teachers' and principals' characteristics on classroom observation ratings. Using data from a statewide teacher evaluation system, we examined whether principals' ratings systematically varied across teachers' characteristics, as well as across shared characteristics between principals and teachers. Our results suggested that principals' ratings varied by teachers' gender, years of experience, and school level, but not by shared demographic characteristics between principals and teachers. Principals rated female, experienced, and elementary teachers more highly than male, novice, and secondary teachers. We discuss implications for research and practice.